Investigating and optimizing bread-making properties of whole wheat flour - Li, Cheng (Kansas State University, 2023)
Whole wheat flour (WWF) is a valuable source of dietary fiber with potential health benefits, making it important for sustainable baking product production. This research aims to optimize the production of high-quality whole wheat bread by investigating the impact of bran particle size, assessing correlations between white flour (WF) and WWF properties, understanding the chemical composition of WWF, and exploring the potential uses of wheat bran extracts. The specific objectives are as follows: 1) Evaluate the effect of bran particle size on the rheology properties and baking quality of WWF from four different varieties; 2) Compare and corelate the bread-making properties of WF and WWF from 64 different genotypes; 3) Investigate the influence of wheat bran chemical composition, lipolytic enzyme activities, and phenolic components and dough rheology and baking properties through correlation analysis; 4) Explore the effects of wheat bran extract on gluten structure, dough rheological, and bread characteristics; 5) Characterize the antioxidant potential and anti-aging effects of xylo-oligosaccharides and peptide hydrolysates extracted from hard and soft wheat brans. The results showed that medium to coarse bran size was more suitable for bread production, while fine bran size was associated with lower specific loaf volume, darker crumb color, and larger hardness value for most wheat varieties. Larger volumes were observed for white bread with higher flour protein content. However, this trend was not consistently observed for WWF. Mixolab tests revealed that WWF had higher water absorption compared to white flour. Strong correlations were observed between WF and WWF for protein content, flour water absorption, pasting properties, and mixing time, while bread volumes and water retention capacity were weakly correlated. Bran lipid content was correlated with mixing peak time, water absorption, water retention capacities, antioxidant capacity, and certain Mixograph properties. Besides, negative correlations were found between mixing peak time and ABTS scavenging capacity, as well as between bran lipoxygenase activity and bread volume. Furthermore, the addition of wheat bran extract (WBE) significantly increased bread volume and enhanced dough properties, including strength, viscosities, and modulus. Scanning electron microscopy analysis revealed the promotion of protein and starch aggregation within the dough by WBE. Xylo-oligosaccharides and peptide hydrolysates derived from hard and soft wheat brans demonstrated significant antioxidant potential and inhibitory effects against collagenase, elastase, and hyaluronidase. Notably, hard wheat bran xylo-oligosaccharide (HXOS) exhibited the highest hyaluronidase inhibition activity (49.9%) at a concentration of 0.5 mg/mL. HXOS comprised 76.8% xylose and arabinose as the major monomeric sugar units, which were significantly higher than those in soft wheat bran xylo-oligosaccharide (SXOS). In terms of peptide hydrolysates, the molecular weight distribution of peptides hydrolysates derived from hard wheat bran (HP) and soft bran (SP) ranged from 1.06 to 17 kDa, with glutamic acid, aspartic acid, and arginine being the most abundant amino acid residues in the peptides. HP contained higher levels of essential and non-essential amino acids, as well as hydrophobic amino acids. Furthermore, HP demonstrated higher total phenolic contents, DPPH and ABTS scavenging activities compared to SP. The total content of hydrophobic amino acids was 163.90 mg/g in HP and 134.50 mg/g in SP. The higher content of hydrophobic amino acids in HP suggests an enhanced potential antioxidants activity and improved interaction with free radicals, thereby offering protection against oxidative damage. This study provides a comprehensive characterization of whole wheat flour, elucidating its composition and bioactive properties. The findings contribute to the understanding of wheat bran's complex nature and its impact on bread quality, while also highlighting the potential of wheat bran extracts for enhancing the nutritional value of bread.
Keywords: Whole wheat flour; Bread quality; Wheat bran composition; Bran bioactives; Bran particle size